PENGEMBANGAN E-LKS LIVEWORKSHEET MELALUI PENDEKATAN SAINTIFIK BERBASIS MASALAH KONTEKSTUAL MATERI BANGUN RUANG SISI DATAR - Zima Ratna Sari; Nahor Murani Hutapea; Elfis Suanto (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Based on the study of the researcher's literature, one of the problems faced by students in learning mathematics is the difficulty with the flat sided space material in terms of instilling concepts. To overcome these problems, an educator can design Student Worksheets (SW) as an effort to help students overcome difficulties in learning. Thus, this study aims to produce an Electronic Student Worksheets (ESW) assisted by liveworksheets through the application of a contextual problem-based scientific approach to valid and practical flat sided geometric material using the Four-D development model. The stages of the Four-D development model are Define, Design, Develop, Disseminate. Grade VIII students of SMP N 40 Pekanbaru (School A) and SMP IT Al-Fityah Pekanbaru (School B) were the subjects of this study. There are two data collection instruments in this study, namely: (1) a validation sheet to see the validity level of the ESW; and (2) student questionnaire sheets to see the level of practicality of the ESW. The results showed that the developed ESW was valid according to the results of expert validation with an average score of 88.97% (very valid criteria). Furthermore, the results of the small group stage show that the ESW is practical with an average score of 83.08% (very practical criteria). Thus the development of ESW is valid and practical and is expected to help students overcome difficulties in understanding the concept of learning material.